Allogeneic and autologous stem cell transplantation for hepatosplenic T-cell lymphoma: a retrospective study of the EBMT Lymphoma Working Party - Tanase, Alina; Dreger, Peter (Leukemia, 2015)
The objective of this registry study was to analyse the outcome of patients who underwent allogeneic or autologous haematopoietic stem cell transplantation (HSCT) for hepatosplenic T-cell lymphoma (HSTL), a rare and extremely aggressive peripheral T-cell lymphoma subtype. Patients were eligible if they had histologically verified HSTL and underwent HSCT between 2003 and 2011. Seventy-six patients were identified in the European Society for Bone and Marrow Transplantation database. Additional baseline and follow-up information could be obtained from the referring centres for 36 patients. Eleven of these were excluded following histopathology review, leaving 25 patients in the final study cohort (alloHSCT 18, autoHSCT 7). With a median follow-up of 36 months, 2 patients relapsed after alloHSCT, resulting in a 3-year progression-free survival of 48%. After autoHSCT, 5 patients relapsed and subsequently died. This study indicates that graft-versus-lymphoma activity conferred by alloHSCT can result in long-term survival for a substantial proportion of patients with HSTL.
Published: 19 September 2014
Gesehen am 29.06.2020